The advertisement call of Allobates niputidea (Anura: Aromobatidae) - Ospina-L., Ana María; Murillo-Bedoya, Daniela; García-Cobos, Daniela; Colón-Piñeiro, Zuania; Acosta-Galvis, Andrés (Zootaxa, 2019)
In anurans, acoustic signal traits are useful for understanding patterns of evolutionary processes, behavioral interactions, and providing diagnostic characters for inferring phylogenetic relationships and delimiting species (Cocroft & Ryan 1995). The advertisement call, which is the vocalization emitted to attract females or segregate conspecific males, is the most conspicuous and studied acoustic signal (Toledo et. al. 2014). However, it remains unknown for many anuran species (Köhler et al. 2017; Guerra et al. 2018).